Unveiling the Hidden Truth: The Evolution and Advancement of Forensic Accounting in Indonesia - Wahyuni-TD, I., S,; bin Zainuddin, Yuserrie; Haron, Hasnah (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
This paper discusses the development of forensic accounting in Indonesia. As Indonesia's economy grows and becomes increasingly interconnected with global markets, the need for effective measures to address financial crimes has become paramount. Forensic accounting, with its unique blend of accounting, investigative skills, and legal knowledge, has emerged as a vital discipline in this context. The forensic accountant is growing in popularity; from the government's perspective, it also takes a special concern. As in Indonesia, fraudulent acts such as corruption, misappropriation of financial statements, fraud and others find out more in a recent year. Thus, it is claimed that forensic accounting should be included in the list of accounting courses in Indonesia.